Overview of Open-Loop Frequency Estimation Techniques for Grid Synchronization of Single-Phase Power Converters - Rahmani, Hachemi; Boulouma, Sabri; Haddadi, Mourad (ENP engineering science journal (En ligne), 2024)
Open-loop synchronization techniques allow to overcome the stability issues to which closed-loop techniques are subject. Most open-loop techniques differ in their Quadratic Signal Generator and their frequency estimation method. In this paper, an overview of the main frequency estimation methods for single-phase power systems is presented. A description of each technique with their structure for numerical implementation is carried out. A comparative study of those frequency estimation methods is performed according to three test scenarios in order to evaluate the robustness of each method. Recommendations for the selection of the technique is given according to the simulation results.